RECURSOS INDIVIDUAIS E ENGAJAMENTO NO TRABALHO - MENDES, DANIEL ROMEIRO (2020)
This study has analyzed the caused impact by individual personal resources on work engagement, checking if the psychological capital had moderated the relationship between happiness character strengths and work engagement, under the Job Demands-Resources (JD-R) theory. It is a field study, quantity, cross sectional, survey. The samples was compounded by 151 workers, 39 years old average age (SD=10), 62% female, and 38% male, 65% married, 87% high school or higher. The majority was from southeast (75%) and more than half (54%) employee (CLT regime), and not in a boss role (60%). The data was collected by Values in Actions Inventory of Strengths (VIA-120), Work Engagement Scale (UWES-9), Psychological Capital Scale (PCQ-21) and through a sociodemographic characteristics questionnaire. The answers were stored in the electronic database and analyzed by descriptive statistics, correlational, ANOVA, and linear regressions. The results has shown that psychological capital and happiness zest character strength has predicted positively the work engagement, showing that psychological capital wasn’t a moderator, but the main predictor. This reveals that more optimistic, hopeful, self-efficacy, and resilient workers, and those ones with more excitement and enthusiasm on their work, they are more engaged at work, this means they show themselves more dedication, vigor, and absorption working. As hypothesized, the workers owning happiness character strengths as signature strengths are more engaged at work than those don’t owning happiness character strengths as signature strengths. This study adds new findings to the literature, because it was not found studies about the relationship among the involved variables together on this study, character strengths, psychological capital, and work engagement together in just one study. On the other hand, the results corroborate with the JD-R model, confirming that personal individual resources explain engagement. It is highlighted on the discussion section that this study doesn’t contemplate the entire model, since it doesn’t investigate job resources and demands, focusing just on the individual resources, as this was its objective. At the end, it is suggested an agenda to amplify the studies on the area.